f(x) = 3/(x + 2) - √x - 3
f(7) = 3/(7 + 2) - √7 - 3
f(7) = 3/9 - √4
f(7) = 0.333 - 2
f(7) = -1.67
AL=5ah!!!!!!!!!! Hope it helps
Answer:
a. 5q+5q+5
Step-by-step explanation:
5q+5q=10q
10q+5 is equivalent to 10q+5
Answer:
The coordinates are
and
.
Step-by-step explanation:
First, we have to derive an expression for translation under the assumption that each point of XYZ experiments the same translation. Vectorially speaking, translation from X to X' is defined by:
(1)
Where
is the vector translation.
If we know that
and
, then the vector translation is:
![T(x,y) = X'(x,y)-X(x,y)](https://tex.z-dn.net/?f=T%28x%2Cy%29%20%3D%20X%27%28x%2Cy%29-X%28x%2Cy%29)
![T(x,y) = (4,7) - (2,3)](https://tex.z-dn.net/?f=T%28x%2Cy%29%20%3D%20%284%2C7%29%20-%20%282%2C3%29)
![T(x,y) = (2, 4)](https://tex.z-dn.net/?f=T%28x%2Cy%29%20%3D%20%282%2C%204%29)
Then, we determine the coordinates for Y' and Z':
![Y'(x,y) = Y(x,y) + T(x,y)](https://tex.z-dn.net/?f=Y%27%28x%2Cy%29%20%3D%20Y%28x%2Cy%29%20%2B%20T%28x%2Cy%29)
![Y'(x,y) = (1,4) + (2,4)](https://tex.z-dn.net/?f=Y%27%28x%2Cy%29%20%3D%20%281%2C4%29%20%2B%20%282%2C4%29)
![Y'(x,y) = (3, 8)](https://tex.z-dn.net/?f=Y%27%28x%2Cy%29%20%3D%20%283%2C%208%29)
![Z'(x,y) = Z(x,y) + T(x,y)](https://tex.z-dn.net/?f=Z%27%28x%2Cy%29%20%3D%20Z%28x%2Cy%29%20%2B%20T%28x%2Cy%29)
![Z'(x,y) =(8,9) + (2,4)](https://tex.z-dn.net/?f=Z%27%28x%2Cy%29%20%3D%288%2C9%29%20%2B%20%282%2C4%29)
![Z'(x,y) = (10, 13)](https://tex.z-dn.net/?f=Z%27%28x%2Cy%29%20%3D%20%2810%2C%2013%29)
The coordinates are
and
.
<span>g(x) = x^3 - 9x^2 + 2x + 48 ?
Probe some roots. When you use x = - 2
you will have: (-2)^3 - 9(-2)^2 + 2(-2) + 48 = -8 - 36 - 4 + 48 = 0
So, - 2 is a root
From that you can divide x^3 - 9x^2 + 2x + 48 by x + 2 and you will get
x^2 - 11x + 24
Then you can factor that: (x - 8)(x - 3)
So, the three roots are x = - 2, x = 3 and x = 8, which is the option B.
Answer: option B. x = 8, x = -2 , and x = 3
</span>